PERKEMBANGAN BAHASA ANAK USIA DINI DAN TEKNIK PENGEMBANGAN DI SEKOLAH - Enny Zubaidah (Jurnal Cakrawala Pendidikan, 2004)
Aged Children Education (EACE) is a part ofpreshool education. The matter of the education, particularly, has been drawn up in government regulation 2003 in the point 28 part I. The regulation stated that EACE is conducted before the elementary education. In developing a language, the teacher needs to have·aknowledge ofthe language development and~he developing oflanguage. Children's language developmenttest in the periodes. The fIrst periode is the pre-lingustic periode which are 0-2 months ofphonation stage in which children learn pronounce the vocal symbols, 2-4 months ofgoing stage, 4-7 months ofexpansion stage in which children begin to produce some new sounds, 7-10 months of cononical stage, 10-14 months of contraction stage in wihch children leam to imitate same sound they listen to. The second is the linguistic period. It includes 12 month children in holofrase periode in which children are able to express a sentence consisting of 3-6 words, 2-3 year children may use the widernouns with the vocabulary of 350 words, 3 year children have vocabulary of 200-300 words. 4 year children are able to use a langusge with the correct stucture and with the vocabulary of 1400-1600 words. 5-6 year children have a correct order of language. The technique ofdeveloping language in schools can be: (a) maximizing natural communication for children, (b) considering the silent period on the early ofthe learning program, (c) using the concrete reference so that 2nd language can be comprehended by children, (d) using the meaning full phrase when the teacher is teaching dialogues, (e) avoiding teaching structure to children, (t) avoiding retenng the LI when teaching L2.